Antagonistic capacity of Trichoderma spp. in vitro against Rhizoctonia solani Kuhn and Fusarium verticillioides Nirenberg (Bioagro, 2020)
The rizoctoniosis (Rhizoctonia solani) and scab (Fusarium verticillioides) are the most important fungal diseases in maize, causing economic losses and deterioration in the quality of the grains. In this research, the antagonistic capacity of Trichoderma spp. against R. solani and F. verticillioides was determined in vitro, in order to identify those isolates with the highest potential to control the mentioned pathogens. Dual culture tests were performed during 14 days, using Petri dishes with potato dextrose agar medium. The evaluation was conducted using a completely randomized design with five replicates. Trichoderma isolates showed significant differences in the variables of percentage of growth inhibition (PGI) and number of sclerotia formed in its interactions with R. solani, and the variables of PGI and percentage of sporulation inhibition in the interaction with F. verticillioides. Also, a general trend was observed favoring the antagonistic capacity of Trichoderma in the variables of percentage of reduction in the number of sclerotia, percentage of sclerotia parasitized and antagonistic degree. The most promising isolates against R. solani were Santa Lucía (T. koningii) and 06142 (T. croseum), while against F. verticillioides they were BAPSOS and I9 (both identified as T. harzianum). Fusarium showed greater resistance to colonization, when compared to Rhizoctonia, by the evaluated Trichoderma species.
Keywords: Biocontrol; percentage of growth inhibition; rizoctoniosis; scab